The influence of catalyst factors for sustainable production of hydrocarbons via Fischer-Tropsch synthesis - Gholami, Z. (Walter de Gruyter GmbH, 2017)
Fischer-Tropsch synthesis (FTS) is a process which catalytically converts syngas (H2 and CO) into clean hydrocarbon fuels. Syngas can be derived from non-petroleum feed stocks such as coal, natural gas or biomass. Increasing the quality of products by development of novel catalysts with high activity and selectivity is desirable in FTS reaction. This article reviews and summarizes recent developments in FTS catalysts and the effects of key factors such as active metals, catalyst supports and promoters on feedstock conversion and product selectivities. © 2017 Walter de Gruyter GmbH, Berlin/Boston.